Les noms propres en LSF : étude à partir d’une traduction - Stéphanie Gobet; Florence Encrevé (Corela)
By definition, a proper noun is the individualising identification of an entity, whether animate or not. In a spoken language, it is specified by its typography, in particular the capital letter or letters when writing. But what about sign languages (SLs), languages whose modality is visual-gestural, which do not have a written system, and whose scriptural function is currently held by the video? Without claiming to give a general definition, we look at the linguistic strategies used to sign certain proper nouns, which have been translated from the corpus under scrutiny. We characterize recurrent forms such as the use of manual proforms and the spatialization of entities, which we analyze in this article.